2016
DOI: 10.1186/s12902-016-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

Reducing major lower extremity amputations after the introduction of a multidisciplinary team in patient with diabetes foot ulcer

Abstract: BackgroundDiabetic foot ulceration is receiving more attention because of its high amputation and mortality rate. It is essential to establish the frequency of amputations in people with diabetes after any change to the management of diabetic foot care. The present study aim to compare the frequency of lower-extremity amputations in patients with diabetes foot ulcer over a ten-year period.MethodsSix hundred forty eight patients with diabetes foot ulcer were retrospectively studied from 2004 to 2013. The clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 15 publications
2
67
1
4
Order By: Relevance
“…9,15,27 Numerous studies and systematic reviews have showed positive effects on multidisciplinary care in reducing wound healing times, amputation rates, and severity of amputation. [28][29][30][31] The definition of multidisciplinary diabetic foot care varies broadly in the literature but often includes a surgeon (general, vascular, and orthopedic), podiatrist, diabetes specialist, physical therapist, and wound care nurse.…”
Section: Multidisciplinary Carementioning
confidence: 99%
“…9,15,27 Numerous studies and systematic reviews have showed positive effects on multidisciplinary care in reducing wound healing times, amputation rates, and severity of amputation. [28][29][30][31] The definition of multidisciplinary diabetic foot care varies broadly in the literature but often includes a surgeon (general, vascular, and orthopedic), podiatrist, diabetes specialist, physical therapist, and wound care nurse.…”
Section: Multidisciplinary Carementioning
confidence: 99%
“…Identification of these high‐risk patients might lead to better and earlier treatment and targeted secondary prevention strategies. A treatment strategy to improve clinical outcome of DFU patients might be the introduction of a multidisciplinary team . It has been shown that the introduction of such a team to DFU care enables to reduce the frequency of major amputations .…”
Section: Introductionmentioning
confidence: 99%
“…Sharp debridement of ulcers, combined with pressure offloading, management of infection and the involvement of a multidisciplinary team to optimise glycaemia, cardiovascular risk, assess potential revascularisation and surgical intervention are considered to be the basis of ulcer care . In order to promote wound healing and reduce risk of amputation, involvement of the multidisciplinary team is recommended early in the natural history of the ulcer …”
Section: Introductionmentioning
confidence: 99%